Improvement of Learning and Memory Deficits With Aerobic Training and Donepezil Co-therapy in Amyloid-β beta-injected Male Rats Through the CREB and BDNF Signaling Pathway - Iman Mohseni; Maghsoud Peeri; Mohammad Ali Azarbayjani (Mazandaran University of Medical Sciences, 2020)
Background: Accumulation of amyloid-β (Aß) plaques, primarily in the hippocampus, leads to neuronal death and Alzheimer disease. Exercise and medications can prevent and treat neuronal diseases. This study aimed to determine the effects of aerobic training and donepezil, a medication used in Alzheimer disease, on the improvement of learning and memory deficits in Aß-injected male rats. Objectives: This ﬆudy aimed to determine the eﬀects of aerobic training and donepezil, a medication used in Alzheimer disease, on the improvement of learning and memory deﬁcits in Aß-injected male rats. Methods: Male Rats were injected with an Aβ solution into their CA1 hippocampal region. After 20 days, the rats were treated with donepezil hydrochloride at doses of 2 mg/kg/d by gavage and following treadmill exercise for 4 weeks. Then, after 24 h, they performed the Morris water maze test for five days. Additionally, we studied the molecular factors involved in neuronal plasticity, such as Ca2+/cAMP-response element-binding protein (CREB) and brain-derived neurotrophic factor (BDNF) on day 33. The animals were also evaluated histologically to determine the deposition of Aβ in the brain tissue. Results: Behavioral analysis showed that in the probe test, the latency to the platform zone significantly increased in the training group (F1,20=6.815; P<0.05) and in the drug group (F1,20=6.369; P<0.05). But there were no significant changes in the combined group compared with the control group (F1,20=3.909; P>0.05). Molecular analysis showed that CREB gene expression improved in the training group (F1,8=9893.539; P<0.01) and in the drug group (F1,8=631.958; P<0.01). But in the combined group, there were no significant changes compared with the Aβ group (F1,8=2.556; P>0.05). BDNF gene expression improved in the training group (F1,8=25.077; P<0.001), and in the drug group (F1,8=45.296; P<0.001). Also, in the combined group, this change was significant compared with the control group (F1,8=64.342; P<0.001). Histomorphometric analysis showed that the density of survived neurons was considerably increased in the combined group (P<0.01), and the drug group (P<0.05) compared to the control group Conclusion: In the present study, behavioral and biochemical analysis demonstrated that aerobic training and donepezil hydrochloride treatment for 4 weeks protect Aβ-injected male rats against memory impairment.